Effectiveness of Teacher Performance Supervision in Implementing the Independent Learning Curriculum at State Vocational High School 7 Tangerang Regency - Hajjah Afi Nashriyah; Rahul Khan (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
This article critically examines an effort to conceptualize a relationship aimed at testing the effectiveness of curriculum supervision on teacher performance in the implementation of the Merdeka Curriculum in vocational high schools (SMK). This study integrates various theoretical perspectives from recent literature. The method used is a qualitative approach with case studies in several vocational high schools that have implemented the Merdeka Curriculum. Data were collected through in-depth interviews with principals, supervisors, and teachers who were directly involved in the curriculum implementation process. The findings show that effective curriculum supervision, which involves regular guidance and constructive feedback, has a positive impact on improving teachers' understanding of curriculum materials and their skills in managing competency-based learning. On the other hand, the lack of coordination between supervisors and teachers, as well as limited supervision time, become obstacles to optimizing implementation. In conclusion, planned and continuous curriculum supervision can improve teacher performance in the application of the Merdeka Curriculum. However, stronger support from school management and supervisors is needed to strengthen the effectiveness of curriculum implementation in vocational high schools. The results of this study are expected to serve as a reference for the development of future educational management models.